Repression and sublimation in religious personalities - Gay, Volney Patrick (Journal of religion and health, 1982)
Like all intense experiencing, religious life is particular: one's feelings are tied to specific people, through specific actions, and in specific contexts. Descriptive typologies, like that of Capps and Capps inThe Religious Personality, reflect the contours of specific selfunderstanding, but by themselves they do not permit one to compare hierarchically the types that sare uncovered. Abstract theoreies, like psychoanalysis, are not particularistic, but they do permit one to conceive of a hierarchy of mental functioning. Capps and Capps's typology of Aesthetic, Chastised, Resigned, and Dfraternal religious selves can be improved by placing each self along the continuum that stretches from repressed (maladaptive) to sublimated (adaptive) functioning.